EXTERNAL FACTORS OF REPUTATION RISK OF ENERGY COMPANIES - E. Pravkina (Вестник университета)
The article discusses the influence of public opinion on the risks and opportunities in the energy companies and, as a consequence, the influence of public opinion on the financial results. The author provides practical examples of implementation of similar situations in Russian and foreign energy companies.